PROTECTIVE ROLE OF WITHAFERIN-A ON RED BLOOD CELL INTEGRITY DURING 7,12-DIMETHYLBENZ[A]ANTHRACENE INDUCED ORAL CARCINOGENESIS - Manoharan, S.; Pamjamurthy, K.; Pugalendi, P.; Balakrishnan, S.; Rajalingam, K.; Vellaichamy, L.; Alias, L. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
The aim of the present study was to investigate the protective effect of Withaferin-A on red blood cell integrity during 7,12-dimethylbenz[a]anthracene (DMBA) induced oral carcinogenesis. The protective effect of Withaferin-A was assessed by measuring the status of glycoconjugates, membrane bound enzyme activity and red blood cell osmotic fragility. Oral squamous cell carcinoma was induced in the buccal pouch of Syrian golden hamsters by painting with 0.5% DMBA in liquid paraffin thrice a week for 14 weeks. The levels of glycoconjugates, membrane bound enzyme activity, osmotic fragility and thiobarbituric acid reactive substances (TBARS) were analyzed by using specific colorimetric methods. We observed 100% tumor formation in DMBA painted hamsters. Increase in plasma glycoconjugates at the expense of red blood cell membrane glycoconjugates levels were observed in DMBA painted hamsters as compared to control hamsters. Erythrocytes from DMBA painted hamsters were more fragile than those from control hamsters. The activity of membrane bound enzyme (Na+ K+ ATPase) decreased whereas TBARS level was increased in DMBA painted hamsters as compared to control hamsters. Oral administration of Withaferin-A at a dose of 20mg kg-1 bw significantly prevented the tumor formation as well as normalized the biochemical variables in DMBA painted hamsters. Our results thus demonstrate the protective effect of Withaferin-A on red blood cell integrity during DMBA induced oral carcinogenesis